2020
DOI: 10.5194/se-11-607-2020
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of core and downhole seismic velocities in high-pressure metamorphic rocks: a case study for the COSC-1 borehole, Sweden

Abstract: Abstract. Deeply rooted thrust zones are key features of tectonic processes and the evolution of mountain belts. Exhumed and deeply eroded orogens like the Scandinavian Caledonides allow us to study such systems from the surface. Previous seismic investigations of the Seve Nappe Complex have shown indications of a strong but discontinuous reflectivity of this thrust zone, which is only poorly understood. The correlation of seismic properties measured on borehole cores with surface seismic data can constrain th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 63 publications
3
28
1
Order By: Relevance
“…Although Almqvist et al (2013) predicted that textural variations along shear zones are in part responsible for seismic reflection observed in the upper and middle crust of orogens, it appears that the mylonitization at the COSC-1 borehole does not change the seismic properties in any significant way, as it does not correlate with changes in the seismic ZOVSP data or the log-derived synthetic seismic data. This is conclusive with previous studies which showed that only some mylonitic rocks with well-developed macroscopic foliation are strongly anisotropic (Jones & Nur, 1982) and with the analysis of the P-wave velocity at the COSC-1 borehole by Wenning et al (2016) and Kästner et al (2020). They showed that the mica schists between 1,600 and 1,900 m have an anisotropy of up to 25% whereas the anisotropy decreases at depths where the mylonite sequences were described (Figure 3e).…”
Section: Origin Of Reflections In the Synthetic Seismogramsupporting
confidence: 92%
See 4 more Smart Citations
“…Although Almqvist et al (2013) predicted that textural variations along shear zones are in part responsible for seismic reflection observed in the upper and middle crust of orogens, it appears that the mylonitization at the COSC-1 borehole does not change the seismic properties in any significant way, as it does not correlate with changes in the seismic ZOVSP data or the log-derived synthetic seismic data. This is conclusive with previous studies which showed that only some mylonitic rocks with well-developed macroscopic foliation are strongly anisotropic (Jones & Nur, 1982) and with the analysis of the P-wave velocity at the COSC-1 borehole by Wenning et al (2016) and Kästner et al (2020). They showed that the mica schists between 1,600 and 1,900 m have an anisotropy of up to 25% whereas the anisotropy decreases at depths where the mylonite sequences were described (Figure 3e).…”
Section: Origin Of Reflections In the Synthetic Seismogramsupporting
confidence: 92%
“…(2017). Nor do the similar P‐wave velocity from the VSP measurements and the sonic log (Figure 4 and Kästner et al., 2020) suggest that small‐scale fractures influence the seismic imaging. Only the reflection at about 200 m depth where acoustic impedance drops (Figure 4) might relate to a texture change.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations